2020
DOI: 10.1177/1937586720901344
|View full text |Cite
|
Sign up to set email alerts
|

Cross-National Comparison of Environmental Factors Important to Facility-Based Senior Living

Abstract: Objective: Focusing on environmental factors important to facility-based senior living, this research intends to identify cross-national similarities and differences in perspective on elderly care between senior-living professionals in the United States and China. Background: American models of senior-living facility design have been introduced in China. In social and cultural context, environmental factors important to facility-based senior living are expected to be different by nation and need to be clarifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Second, our participants were older adults residing in RCFs in Northeast China; thus, our findings are not easily generalizable to other populations and geographic locations. Previous research has shown that there are differences between different cultures in terms of preference; for example, older adults in the United States are more inclined to emphasize the importance of residents’ rooms while Chinese residents are more interested in natural lighting that could fulfill their psychological needs (Z. Wang, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, our participants were older adults residing in RCFs in Northeast China; thus, our findings are not easily generalizable to other populations and geographic locations. Previous research has shown that there are differences between different cultures in terms of preference; for example, older adults in the United States are more inclined to emphasize the importance of residents’ rooms while Chinese residents are more interested in natural lighting that could fulfill their psychological needs (Z. Wang, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that there are differences between different cultures in terms of preference; for example, older adults in the United States are more inclined to emphasize the importance of residents' rooms while Chinese residents are more interested in natural lighting that could fulfill their psychological needs (Z. Wang, 2020). Third, the detailed needs and views of different age groups and genders with respect to the physical environment were not analyzed in this study; we hope to study these elements in the future to comprehensively explore the interactions among physical factors.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite having roots in North America, AL is emerging as a mainstream model and philosophy of care for older people and is increasingly being adopted in ageing Asian countries [14][15][16][17]. With the changing demographic structures in many industrialised countries whereby the need for residential care services has increased dramatically, AL will emerge as an increasingly popular long-term care model due to its privacy-and autonomypreserving characteristics [18].…”
Section: The Global Phenomenon Of Ageing Population and The Need For Service Diversification In Long-term Carementioning
confidence: 99%
“…Importantly, outdoor environments for physical activities (e.g., walking routes) should be provided on facility sites to promote residents' active living. With good natural ventilation, the outdoor environments may be developed into safe common areas with low risk of infection, which are important to institutionalized senior living (Wang, 2020). The rules of social distancing should be followed, and more research is needed to promote residents' active living during the difficult time of facility lockdown.…”
Section: At the Site Levelmentioning
confidence: 99%